1985
DOI: 10.1159/000309582
|View full text |Cite
|
Sign up to set email alerts
|

Electron-Microscopic Study of Iris Nerves and Muscles in Diabetes

Abstract: The ultrastructure of the iris muscles and innervating nerves in patients with diabetes mellitus and approximately age-matched controls was examined by electron-microscopy. The specimens were obtained during cataract surgery. There were definite histopathological alterations at the nerve terminal innervating the dilator muscle, e. g. the presence of mitochondrial abnormalities, dense bodies and lamellar structures. No change was noted at the nerve terminal to the sphincter muscle. Moderate involvement of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

1988
1988
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 9 publications
(11 reference statements)
0
10
0
1
Order By: Relevance
“…It has been thought that failure of the sympathetic nerve 10,19−21 and pathological changes 22 in the iris muscles of diabetics are the cause of the reduced dark-adapted pupil size in diabetics. Moreover, Ishikawa et al 23 showed that, in diabetics, normal nerve endings were present in the sphincter, while a few degenerated nerve endings were observed only in the nerve innervating the dilator muscle, suggesting sympathetic damage. Smith and Smith 20 measured resting pupil diameter and the amplitude of the reflex response to standard light flashes in background darkness and found that the diabetic subjects had small pupils but their reflexes were much smaller for a given resting diameter than those of healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…It has been thought that failure of the sympathetic nerve 10,19−21 and pathological changes 22 in the iris muscles of diabetics are the cause of the reduced dark-adapted pupil size in diabetics. Moreover, Ishikawa et al 23 showed that, in diabetics, normal nerve endings were present in the sphincter, while a few degenerated nerve endings were observed only in the nerve innervating the dilator muscle, suggesting sympathetic damage. Smith and Smith 20 measured resting pupil diameter and the amplitude of the reflex response to standard light flashes in background darkness and found that the diabetic subjects had small pupils but their reflexes were much smaller for a given resting diameter than those of healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…The sympathetic pupillary fibers are longer than the parasympathetic fibers and therefore seem to be more vulnerable than the oculomotor fibers [49 -51]. In irides removed during cataract surgery in diabetic patients, loss of nerve terminals occurs mostly from the sympathetically innervated dilator pupillae [54].…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies have demonstrated that sympathetic innervation is critical in the regulation of choroidal vascularization [73], and that the chronic loss of sympathetic activity can contribute to the anomalous vascular proliferation noted in diseases such as age-related macular degeneration (ARMD) [74] and diabetic retinopathy [75,76]. Furthermore, the loss of this innervation can cause oedema in the retina [71], a circumstance that could be important in illnesses such as diabetes or hypertension, in which automatic control is altered [56].…”
Section: Neural Control Of Choroidal Blood Flow In Ocular Diseasesmentioning
confidence: 99%